Hubungan Kadar Debu Total, Karakteristik Pekerja, Dan Perilaku Individu Terhadap Keluhan Subjektif Gangguan Pernapasan Pada Tenaga Kerja Bongkar Muat (TKBM) Di Pelabuhan Marunda, Jakarta Utara Tahun 2023 - Budi Pramono; Atang Saputra; Syarifuddin; Syathiroh (CV. Multi Kreasi Media, 2023)
Air pollution is an event of mixing of harmful elements, both chemical, physical and biological elements in one atmosphere which can have a negative impact on living things and their environment. One of the substances of air pollution is dust. Dust will become dangerous if inhaled into the human respiratory tract and cause respiratory problems. This study entitled